2019
DOI: 10.1038/s41598-019-38815-0
|View full text |Cite
|
Sign up to set email alerts
|

Optical bleaching front in bedrock revealed by spatially-resolved infrared photoluminescence

Abstract: Optically stimulated luminescence (OSL) dating of sediment, based on the accumulation of trapped charge in natural crystals since their last exposure to daylight, has revolutionised our understanding of the late Quaternary period. Recently, a complementary technique called luminescence rock surface dating (RSD), which uses differential spatial eviction of trapped charges in rocks exposed to daylight, has been developed to derive exposure and burial ages, and hard-rock erosion rates. In its current form, the RS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 62 publications
3
21
0
Order By: Relevance
“…The available spatial resolution in this study (because of cross-talk) restricted interpretations at the sub-grain level, and furthermore, only one IRPL emission (955 nm emission) was examined. Similarly, Sellwood et al 22 have shown that IRPL (955 nm emission) is correlated with K concentration in feldspar in granitic rocks.…”
Section: Introductionmentioning
confidence: 74%
“…The available spatial resolution in this study (because of cross-talk) restricted interpretations at the sub-grain level, and furthermore, only one IRPL emission (955 nm emission) was examined. Similarly, Sellwood et al 22 have shown that IRPL (955 nm emission) is correlated with K concentration in feldspar in granitic rocks.…”
Section: Introductionmentioning
confidence: 74%
“…In conclusion, based on the novel RPL/OSL system, we are able to infer for the first time that the thermal dependence of the IRSL curve can largely be attributed to process d), i.e., depletion of holes because of competitive recombination. This is radically different interpretation of pulse anneal curves which are commonly believed to arise from the thermal erosion of the electrons in the principal trap (e.g., 41 ), or from localised e-h recombination (e.g., 25 ). Furthermore, we establish that TL and IRSL may not arise from the same electron trap, instead both the processes use the same hole traps.…”
Section: Pir 50 Irpl (T)/pir 50 Irpl (Test Dose): Sensitivity Correctmentioning
confidence: 93%
“…1 c. Each defect can emit IRPL at the rate of thousands of photons per second dependent on the excitation rate. This provides an unprecedented sensitivity for 2D 25 and 3D mapping of defect distribution and examination of charge transfer in future.
Figure 1 ( a ) Band diagram showing the OSL (using near infrared excitation: IRSL) and the IRPL process from the principal trap; this constitutes a coupled RPL/OSL system.
…”
Section: Introductionmentioning
confidence: 99%
“…Rock slices (between 0.4 and 1.2 mm in thickness) are likely to be especially prone to thermal lag because of their mass (e.g. Fig 1a of Sellwood et al 2019), and both of the approaches described here have been adopted to mitigate this problem (e.g. Sohbati et al 2015 use a pause of 30s between reaching the desired measurement temperature and starting optical stimulation, while Jenkins et al…”
Section: Implications For Other Types Of Luminescence Measurementsmentioning
confidence: 99%